Evaporation‐induced Self‐assembly Process Controlled for Obtaining Highly Ordered Mesoporous Materials with Demanded Morphologies. Issue 1 (25th January 2016) - Kimura, Tatsuo
Abstract: A large number of periodic mesoporous materials have been reported using amphiphilic organic molecules with increasing development of synthetic methods for mesostructural, morphological, and compositional designs. The evaporation‐induced self‐assembly (ESIA) process to fabricate ordered mesoporous films is one of the most essential synthetic methods, which has extensively been applied for obtaining a wide variety of samples (e.g., films and monoliths, including powders). It contains complicated physical variations and chemical reactions, but has been simply explained by several research groups. However, a current, exact understanding of such complicated systems should be given with respect to all the variations and reactions. In this article, I have mainly surveyed the exact EISA process by considering the difference between simple and controlled EISA processes on the basis of my own experiments. I believe that the insights are consequently helpful for obtaining highly ordered mesoporous materials with demanded morphologies. Abstract : The concept of the "controlled EISA process" has been proposed on the basis of the overall self‐assembly process of not only amphiphilic inorganic‐organic pairs, but also free inorganic species and/or extra surfactant molecules, which are accommodated in a final mesostructured material, in which all of them can be tiled closely to fabricate a highly ordered mesostructure.